Study of Flood Risk Assessment on Banyumas and Cilacap District in Downstream Serayu River Basin, Indonesia - Kirana, Pratita Hana; Farid, Mohammad; Bagus Adityawan , Mohammad; Kuntoro, Arno Adi; Widyaningtyas, Widyaningtyas (Jurnal Teknik Sipil, 2023)
Abstract. Floods due to the Downstream Serayu River overflow inundate agricultural land and houses in parts of Banyumasand Cilacap district every year. Based on the classification of flood hazard level referring to Chief of BNPBRegulation Number 2 the Year 2012 on General Guidelines for Assessment of Disaster Risk, some location pointsexperienced a high level of flood hazard (>1.5 m). The objective of this study is to develop a flood risk map by usingGIS. Flood hazard assessment uses the HEC-RAS 5.0.6 two-dimensional model, verified with field observation data.The river discharge is obtained from hydrological calculations, while the tidal component is obtained usingMATLAB-LP Tides BIG. River geometry uses river cross-section from field measurement data for hydraulicmodeling combined with MERIT DEM as its banks. The capacity level also refers to the BNPB Number 2 the Year2012. In this study, BNPB and PUPR parameters are used. The vulnerability component refers to a 2014 study fromthe Ministry of Public Work and Housing (PUPR) Indonesia. The 50-year flood return period shows that the totalarea of risk flooded areas in the Downstream Serayu River Basin is 6.22 km2, while high-risk flooded areas are 2.2 km2. Keywords: Flood risk, HEC-RAS 2D, GIS, MATLAB–LP Tides BIG, MERIT DEM Abstrak. Banjir akibat luapan Sungai Serayu Hilir setiap tahun menggenangi lahan pertanian dan perumahan di sebagianwilayah Kabupaten Banyumas dan Cilacap. Berdasarkan klasifikasi tingkat bahaya banjir mengacu padaPeraturan Kepala BNPB Nomor 2 Tahun 2012 tentang Pedoman Umum Pengkajian Risiko Bencana, beberapa titiklokasi mengalami tingkat bahaya banjir tinggi (>1,5 m). Tujuan dari penelitian ini yaitu mengembangkan petarisiko banjir dengan menggunakan SIG. Pemodelan banjir menggunakan model dua dimensi HECRAS 5.0.6, yangdiverifikasi dengan data observasi lapangan. Debit sungai diperoleh dari perhitungan hidrologi, sedangkankomponen pasang surut diperoleh dari perhitungan menggunakan MATLAB-LP Tides BIG. Geometri sungaimenggunakan penampang sungai dari data pengukuran lapangan untuk pemodelan hidrolik yang dikombinasikandengan MERIT DEM sebagai bantarannya. Tingkat kapasitas juga mengacu pada Peraturan Kepala BNPB Nomor2 Tahun 2012. Dalam penelitian ini digunakan parameter BNPB dan PUPR. Komponen kerentanan mengacu padastudi tahun 2014 dari Kementerian Pekerjaan Umum dan Perumahan Rakyat (PUPR) Indonesia. Periode ulangbanjir 50 tahun menunjukkan bahwa total luas area yang berisiko banjir di DAS Serayu Hilir sebesar 6,22 km2,sedangkan area dengan tingkat risiko banjir tinggi sebesar 2,2 km2. Kata-kata Kunci: Risiko banjir, HEC-RAS 2D, SIG, MATLAB–LP Tides BIG, MERIT DEM